THE RESONANT RESPONSE OF STRONGLY COUPLED NANORODS TO THE ELECTROMAGNETIC WAVE - Manukyan, Davit A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2023)
The electromagnetic response of closely spaced nanorod dimers can be controlled via the modification of the nanoparticles interaction, caused by electron tunneling between them. The optical response to an intense external electromagnetic field of a system composed of two gold 230 nm long rods surrounded by air and separated by a gap of width 0.5 nm was analyzed. Using finite element method-based numerical simulations we show that the electron tunneling, taking place due to the extraordinary enhancement of the electromagnetic field inside the nanogap, results in the change of the nanoantenna coupling from the capacitive to the conductive one. As a result, the absorption-to-scattering ratio of the dimer significantly changes. Particularly, the scattering cross-section decreases by about three times, whereas the normalized absorption rises from about 12 to 18 with noticeably broadening of the spectral line.
Keywords: electron tunneling; nanorods; absorption; scattering; field enhancement